2014
DOI: 10.1212/wnl.0000000000001079
|View full text |Cite
|
Sign up to set email alerts
|

Mutant SNAP25B causes myasthenia, cortical hyperexcitability, ataxia, and intellectual disability

Abstract: Objective: To identify and characterize the molecular basis of a syndrome associated with myasthenia, cortical hyperexcitability, cerebellar ataxia, and intellectual disability.Methods: We performed in vitro microelectrode studies of neuromuscular transmission, performed exome and Sanger sequencing, and analyzed functional consequences of the identified mutation in expression studies.Results: Neuromuscular transmission at patient endplates was compromised by reduced evoked quantal release. Exome sequencing ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
112
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 39 publications
1
112
0
Order By: Relevance
“…In conclusion, the identification of biallelic variants in VAMP1 as a novel cause of CMS, in addition to other genes (eg, SNAP25B, SYT2 ) previously associated with similar presynaptic abnormalities of neuromuscular transmission,5, 6 highlights the crucial role of different SNAREs in NMJ physiology. Intriguingly, the relatively mild phenotype showed by our patients compared to the mouse model, which dies prematurely, suggests the possible existence of species‐specific compensation of vesicle fusion and release at the nerve terminal, perhaps through genetic modifiers in humans but not in mice or fruit flies.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In conclusion, the identification of biallelic variants in VAMP1 as a novel cause of CMS, in addition to other genes (eg, SNAP25B, SYT2 ) previously associated with similar presynaptic abnormalities of neuromuscular transmission,5, 6 highlights the crucial role of different SNAREs in NMJ physiology. Intriguingly, the relatively mild phenotype showed by our patients compared to the mouse model, which dies prematurely, suggests the possible existence of species‐specific compensation of vesicle fusion and release at the nerve terminal, perhaps through genetic modifiers in humans but not in mice or fruit flies.…”
Section: Discussionmentioning
confidence: 77%
“…Several molecular causes can be implicated in CMS pathophysiology, including mutations in genes encoding proteins associated with the muscle nicotinic acetylcholine receptor and the synaptic basal lamina, or (more rarely) involved in the NMJ presynaptic transmission 2, 3, 4, 5, 6…”
mentioning
confidence: 99%
“…Of note, a patient with SNAP25 mutation also benefited from 3,4-DAP treatment but not from pyridostigmine, emphasizing the similarity in presynaptic pathophysiology. 7 We describe the clinical and neurophysiologic features of a novel human neuromuscular syndrome caused by autosomal-dominant mutations in the synaptic vesicle calcium sensor SYT2. The phenotype of this mutation is suggestive of a distal hereditary neuropathy.…”
mentioning
confidence: 99%
“…Deficiency of SNAP25B was reported with an autosomal dominant pattern of CMS presenting in an 11-year-old African-American female patient with a history of intrauterine hypotonia, cyanosis at birth, delayed psychomotor development, multiple joint contractures, muscle weakness, fatigable ptosis, associated with ataxia and early childhood epilepsy, whose biomolecular studies revealed a decrease in the amount of acetylcholine released from the presynaptic nerve terminal from each motor nerve impulse 4,18 .…”
Section: Deficiency Of Snap25b (Omim #616330)mentioning
confidence: 99%